A composite polyester fiber and a method for preparing the same

CN122918731APending Publication Date: 2026-10-16FOSHAN NANHAI ZHONGYUESHUN JACQUARD WEAVING IND CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610920272.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-24
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

但在实际使用与应用场景拓展过程中,常规涤纶纤维的固有特性带来了较为突出的安全与使用缺陷,限制了其在高安全性要求领域的应用

Benefits of technology

[0017]其中,聚(3,4-亚乙二氧基噻吩)-聚(苯乙烯磺酸)和水性聚氨酯预聚体的质量之和在浸渍液中的质量占比为5%-10%;

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The application belongs to the technical field of textile fibers, and discloses a kind of composite polyester fiber and its preparation method, composite polyester fiber includes fiber main body and the first coating layer covered on the surface of fiber main body;Wherein, fiber main body is obtained by melt blending spinning of first raw material, and first raw material includes, by weight fraction, polyethylene terephthalate chip 72-78 parts, toughening agent 6-10 parts, aluminum diethyl phosphinate 9-13 parts, nano zinc oxide 2-4 parts, inorganic filler 1-2 parts, lubricant 1-1.5 parts;The first coating layer includes water-based polyurethane and poly (3,4-ethylenedioxythiophene) -poly (styrene sulfonic acid) uniformly dispersed in water-based polyurethane.The application is designed by the synergistic adaptation of the internal flame-retardant modification system of fiber main body and the surface antistatic functional coating, effectively solves the core safety problem that traditional polyester fiber static hazard and flammable risk are mutually superimposed from two levels of eliminating static ignition inducement and blocking combustion spread path.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application belongs to the field of textile fiber technology, and specifically relates to a composite polyester fiber and its preparation method. Background Technology

[0002] Polyester, a synthetic fiber made of polyethylene terephthalate, is widely used in textiles, apparel, industrial fabrics, and interior materials due to its excellent mechanical strength, abrasion resistance, chemical corrosion resistance, and mature processing technology. It is currently the most widely used mainstream synthetic fiber. However, in practical use and application expansion, the inherent characteristics of conventional polyester fibers bring significant safety and usage defects, limiting its application in fields with high safety requirements. Conventional polyester fibers are flammable and easily ignited when exposed to open flames or high temperatures. The combustion process is accompanied by melting and dripping, and rapid flame spread, posing safety risks. Furthermore, during production, processing, and daily use, polyester fibers easily generate and accumulate static electricity through friction and peeling. This static electricity accumulation not only causes dust adsorption and entanglement during processing, but more importantly, the sparks generated by electrostatic discharge can become a direct ignition source, significantly increasing the probability of polyester fibers igniting. This creates a synergistic effect between static electricity hazards and flammability hazards, further exacerbating safety risks during use. Summary of the Invention

[0003] This application aims to improve at least one technical problem in the background art.

[0004] The first aspect of this application provides a composite polyester fiber, including a fiber body and a first coating covering the surface of the fiber body; The fiber body is obtained by melt blending and spinning of the first raw material, which includes, by weight parts: 72-78 parts of polyethylene terephthalate chips, 6-10 parts of toughening agent, 9-13 parts of aluminum diethylphosphinate, 2-4 parts of nano zinc oxide, 1-2 parts of inorganic filler, and 1-1.5 parts of lubricant. The first coating comprises waterborne polyurethane and poly(3,4-ethylenedioxythiophene)-poly(styrene sulfonic acid) uniformly dispersed in the waterborne polyurethane, wherein the waterborne polyurethane is obtained by crosslinking a waterborne polyurethane prepolymer.

[0005] The composite polyester fiber provided in this application uses polyethylene terephthalate (PET) chips as the matrix material, which is spun after multi-component melt blending. PET chips provide the basic structural strength and melt processing performance of the fiber, ensuring the fiber's forming stability and strength in normal use. Toughening agents are used to adjust the mechanical properties of the fiber, improve the overall flexibility of the fiber, and avoid the problem of increased fiber brittleness caused by the introduction of other functional components. As a core flame retardant component, aluminum diethylphosphinate can capture active free radicals generated during combustion when the fiber is heated or comes into contact with a fire source, interrupting the chain reaction of combustion, and at the same time promoting the formation of a continuous barrier structure on the fiber surface to block the entry of external oxygen and the transfer of internal heat. Nano zinc oxide and aluminum diethylphosphinate work together to further enhance the density and heat resistance of the above barrier structure, making the flame retardant effect of the fiber more durable and efficient. Inorganic fillers can optimize the uniformity of component distribution inside the fiber and reduce internal defects. Lubricants can reduce the frictional resistance of each component during melt blending and spinning, improve the fluidity of the melt, and ensure continuous and stable fiber forming. The first coating on the fiber substrate uses poly(3,4-ethylenedioxythiophene)-poly(styrene sulfonic acid) as the conductive functional component. This component can form continuous conductive channels on the fiber surface, quickly dissipating the static charge generated during fiber use and preventing the accumulation of static electricity. Waterborne polyurethane is the film-forming base component of the coating, forming a continuous and uniform film on the fiber substrate. It interacts with poly(3,4-ethylenedioxythiophene)-poly(styrene sulfonic acid) (waterborne polyurethane prepolymers usually contain unreacted free isocyanate groups, while poly(3,4-ethylenedioxythiophene)-poly(styrene sulfonic acid) contains sulfonic acid groups. The reaction between the two allows poly(3,4-ethylenedioxythiophene)-poly(styrene sulfonic acid) to bond to the three-dimensional network of waterborne polyurethane), making the conductive component stably fixed in the film layer. At the same time, it allows the coating to be tightly bonded to the fiber substrate, making it less prone to cracking and peeling, and maintaining the long-term effectiveness of the antistatic function.

[0006] Conventional polyester fibers are prone to static electricity buildup during use. Sparks generated by electrostatic discharge can act as ignition sources, igniting the polyester material itself and posing a safety hazard. This application addresses this issue by synergistically combining the antistatic properties of the surface coating with the flame-retardant properties of the flame-retardant components within the fiber matrix. The antistatic coating rapidly dissipates static charge, eliminating the key ignition source—static sparks—at its source. Meanwhile, the flame-retardant components within the fiber matrix can block the combustion reaction process under extreme conditions, inhibiting the occurrence and spread of combustion. These two functions comprehensively improve the safety of the fiber from both "ignition prevention" and "combustion suppression" perspectives, making it suitable for applications requiring both electrostatic protection and flame-retardant performance.

[0007] Preferably, the mass ratio of poly(3,4-ethylenedioxythiophene)-poly(styrene sulfonic acid) to waterborne polyurethane prepolymer is 1:(1-2). At this specific mass ratio, in the final first coating, poly(3,4-ethylenedioxythiophene)-poly(styrene sulfonic acid) can form continuous and uniform conductive channels, ensuring rapid discharge of static charge. Simultaneously, the waterborne polyurethane can fully encapsulate the conductive components and tightly bond with the fiber surface. This prevents the coating from experiencing reduced adhesion or easy detachment due to excessive conductive components, and also prevents excessive film-forming components from masking the conductive effect, thus giving the coating both long-lasting antistatic properties and good adhesion.

[0008] Preferably, the thickness of the first coating is 0.1μm-0.5μm. This thickness range can balance the antistatic function and the performance of the fiber itself, ensuring the formation of a continuous conductive network to achieve a stable antistatic effect. At the same time, the coating will not clump or harden due to excessive thickness, avoiding adverse effects on the flexibility and textile processability of the fiber, nor will it break the conductive path or fail to perform the antistatic function due to excessive thinness, thus maintaining a good balance between the coating function and the fiber's performance.

[0009] Preferably, the particle size of aluminum diethylphosphinate is 0.5 μm-3 μm. This particle size range ensures that the flame-retardant component is uniformly dispersed in the polyethylene terephthalate matrix, preventing agglomeration due to excessively small particle size and avoiding clogging of the spinneret and affecting spinning continuity during melt spinning due to excessively large particle size. The suitable particle size allows aluminum diethylphosphinate to fully exert its free radical scavenging effect and achieves more sufficient contact with nano-zinc oxide, resulting in a more stable synergistic flame-retardant effect and thus ensuring the uniformity of the overall flame-retardant efficiency of the fiber.

[0010] Preferably, the particle size of the nano-zinc oxide is 50nm-80nm. This particle size range allows the nano-zinc oxide to maintain a good dispersion state in the fiber matrix, avoiding stress concentration and reduced fiber mechanical properties caused by large-particle inorganic particles. The nano-zinc oxide in this particle size range has a moderate specific surface area, enabling it to efficiently combine with aluminum diethylphosphinate to enhance the densification and thermal stability of the condensed phase barrier layer. Simultaneously, it avoids agglomeration during processing due to excessively small particle size, ensuring the stable performance of the flame-retardant synergistic effect.

[0011] Preferably, the intrinsic viscosity of polyethylene terephthalate (PET) chips is 0.65 dL / g to 0.8 dL / g. This intrinsic viscosity range allows the matrix melt to possess suitable fluidity and strength during melt spinning. The melt can smoothly pass through the spinneret to form fibers, reducing processing defects such as broken fibers and fuzz, while ensuring that the fibers have good basic mechanical strength and molecular chain integrity after forming. This provides stable matrix support for the subsequent dispersion and functional realization of various functional components, and is suitable for the processing requirements of melt blending spinning.

[0012] Preferably, the toughening agent includes at least one of polycaprolactone, polybutylene succinate, and polybutene-1.

[0013] Preferably, the inorganic filler includes at least one of nano-calcium carbonate, nano-silica, nano-montmorillonite, and nano-talc.

[0014] Preferably, the lubricant includes at least one of ethylene bis-stearamide, calcium stearate, zinc stearate, and pentaerythritol stearate.

[0015] The second aspect of this application provides a method for preparing the above-mentioned composite polyester fiber, comprising the following steps: Polyethylene terephthalate chips, toughening agent, aluminum diethylphosphinate, nano zinc oxide, inorganic filler and lubricant are mixed and then melt-blended and spun to obtain the fiber matrix; Poly(3,4-ethylenedioxythiophene)-poly(styrenesulfonic acid) and waterborne polyurethane prepolymer were added to water, mixed well, and the impregnation solution was prepared. The fiber body is immersed in the impregnation solution, then taken out, rolled, and dried to obtain composite polyester fiber.

[0016] The melt blending temperature in melt blending spinning is 265℃-280℃.

[0017] The total mass of poly(3,4-ethylenedioxythiophene)-poly(styrene sulfonic acid) and waterborne polyurethane prepolymer in the impregnation solution accounts for 5%-10% of the total mass. The slurry yield of the roll forming process is 60%-75%.

[0018] The drying temperature is 120℃-135℃, and the drying time is 2min-10min.

[0019] The beneficial effects of this application are as follows: This application, through the synergistic adaptation design of the flame-retardant modification system inside the fiber body and the antistatic functional coating on the surface, effectively solves the core safety problem of the superposition of static electricity hazards and flammability risks in traditional polyester fibers from two aspects: eliminating the causes of static ignition and blocking the path of combustion spread. The overall technical solution takes into account functional synergy, structural stability and application durability. Without compromising the basic performance of the fiber, it simultaneously improves the dual safety performance of flame retardancy and antistatic properties, effectively broadening the application scope of polyester fibers in various high-safety-requirement scenarios, and has significant technical advantages and practical application value. Detailed Implementation

[0020] The present application will be further described below with reference to specific embodiments. It should be understood that these embodiments are for illustrative purposes only and are not intended to limit the scope of the application. Furthermore, it should be understood that after reading the contents of this application, those skilled in the art can make various alterations or modifications to this application, and these equivalent forms also fall within the scope defined by the appended claims.

[0021] Example 1 A composite polyester fiber includes a fiber body and a first coating (0.3 μm thick) covering the surface of the fiber body.

[0022] The fiber body is obtained by melt blending and spinning of the first raw material, which includes, by weight, 75 parts of polyethylene terephthalate chips (intrinsic viscosity of 0.70 dL / g), 8 parts of toughening agent (polycaprolactone), 11 parts of aluminum diethylphosphinate (particle size of 1.5 μm), 3 parts of nano zinc oxide (particle size of 60 nm), 1.5 parts of inorganic filler (nano silica), and 1.2 parts of lubricant (ethylene bis-stearamide).

[0023] The first coating comprises waterborne polyurethane and poly(3,4-ethylenedioxythiophene)-poly(styrene sulfonic acid) uniformly dispersed in the waterborne polyurethane. The waterborne polyurethane is obtained by crosslinking the waterborne polyurethane prepolymer, and the mass ratio of poly(3,4-ethylenedioxythiophene)-poly(styrene sulfonic acid) to the waterborne polyurethane prepolymer is 1:1.5.

[0024] The method for preparing this composite polyester fiber includes the following steps: Mix polyethylene terephthalate chips, toughening agent, aluminum diethyl phosphinate, nano zinc oxide, inorganic filler and lubricant (mix at 1000 r / min for 15 min in a high-speed mixer). Melt blending spinning is performed by first feeding the above-mentioned homogenized mixture into a twin-screw extruder for melt blending (temperature 270℃), extrusion (screw speed 250r / min), and then feeding it into a spinning machine for spinning. After spinning, the mixture is air-cooled, stretched and shaped to obtain the fiber body. Poly(3,4-ethylenedioxythiophene)-poly(styrene sulfonic acid) and waterborne polyurethane prepolymer were added to water and mixed to prepare an impregnation solution (the total mass of poly(3,4-ethylenedioxythiophene)-poly(styrene sulfonic acid) and waterborne polyurethane prepolymer accounted for 7% of the mass of the impregnation solution). The fiber body is immersed in the impregnation solution for 30 seconds, then taken out and rolled (with a liquid rate of 70%), dried (drying temperature of 125℃ and drying time of 5 minutes), and wound to obtain composite polyester fiber.

[0025] Example 2 A composite polyester fiber includes a fiber body and a first coating (0.1 μm thick) covering the surface of the fiber body.

[0026] The fiber body is obtained by melt blending and spinning of the first raw material, which includes, by weight parts: 72 parts of polyethylene terephthalate chips (intrinsic viscosity of 0.65 dL / g), 6 parts of toughening agent (polycaprolactone), 9 parts of aluminum diethylphosphinate (particle size of 0.5 μm), 2 parts of nano zinc oxide (particle size of 50 nm), 1 part of inorganic filler (nano calcium carbonate), and 1.0 part of lubricant (ethylene bis-stearamide).

[0027] The first coating comprises waterborne polyurethane and poly(3,4-ethylenedioxythiophene)-poly(styrene sulfonic acid) uniformly dispersed in the waterborne polyurethane. The waterborne polyurethane is obtained by crosslinking the waterborne polyurethane prepolymer, and the mass ratio of poly(3,4-ethylenedioxythiophene)-poly(styrene sulfonic acid) to the waterborne polyurethane prepolymer is 1:1.

[0028] The method for preparing this composite polyester fiber includes the following steps: Mix polyethylene terephthalate chips, toughening agent, aluminum diethyl phosphinate, nano zinc oxide, inorganic filler and lubricant (mix at 1000 r / min for 15 min in a high-speed mixer). Melt blending spinning is performed by first feeding the above-mentioned homogenized mixture into a twin-screw extruder for melt blending (temperature 265℃), extrusion (screw speed 250r / min), and then feeding it into a spinning machine for spinning. After spinning, the mixture is air-cooled, stretched and shaped to obtain the fiber body. Poly(3,4-ethylenedioxythiophene)-poly(styrene sulfonic acid) and waterborne polyurethane prepolymer were added to water and mixed to prepare an impregnation solution (the total mass of poly(3,4-ethylenedioxythiophene)-poly(styrene sulfonic acid) and waterborne polyurethane prepolymer accounted for 5% of the mass of the impregnation solution). The fiber body is immersed in the impregnation solution for 30 seconds, then taken out and rolled (the liquid rate is 60%), dried (the drying temperature is 120℃ and the drying time is 2 minutes), and wound to obtain composite polyester fiber.

[0029] Example 3 A composite polyester fiber includes a fiber body and a first coating (0.5 μm thick) covering the surface of the fiber body.

[0030] The fiber body is obtained by melt blending and spinning of the first raw material, which includes, by weight parts: 78 parts of polyethylene terephthalate chips (intrinsic viscosity of 0.80 dL / g), 10 parts of toughening agent (polybutylene succinate), 13 parts of aluminum diethylphosphinic acid (particle size of 3 μm), 4 parts of nano zinc oxide (particle size of 80 nm), 2 parts of inorganic filler (nano silica), and 1.5 parts of lubricant (ethylene bis-stearamide).

[0031] The first coating comprises waterborne polyurethane and poly(3,4-ethylenedioxythiophene)-poly(styrene sulfonic acid) uniformly dispersed in the waterborne polyurethane. The waterborne polyurethane is obtained by crosslinking the waterborne polyurethane prepolymer, and the mass ratio of poly(3,4-ethylenedioxythiophene)-poly(styrene sulfonic acid) to the waterborne polyurethane prepolymer is 1:2.

[0032] The method for preparing this composite polyester fiber includes the following steps: Mix polyethylene terephthalate chips, toughening agent, aluminum diethyl phosphinate, nano zinc oxide, inorganic filler and lubricant (mix at 1000 r / min for 15 min in a high-speed mixer). Melt blending spinning is performed by first feeding the above-mentioned homogenized mixture into a twin-screw extruder for melt blending (temperature 280℃), extrusion (screw speed 250r / min), and then feeding it into a spinning machine for spinning. After spinning, the mixture is air-cooled, stretched and shaped to obtain the fiber body. Poly(3,4-ethylenedioxythiophene)-poly(styrene sulfonic acid) and waterborne polyurethane prepolymer were added to water and mixed to prepare an impregnation solution (the total mass of poly(3,4-ethylenedioxythiophene)-poly(styrene sulfonic acid) and waterborne polyurethane prepolymer accounted for 10% of the mass of the impregnation solution). The fiber body is immersed in the impregnation solution for 30 seconds, then taken out and rolled (with a liquid rate of 75%), dried (at a temperature of 135°C for 10 minutes), and wound to obtain composite polyester fiber.

[0033] Example 4 A composite polyester fiber differs from Example 1 in that the mass ratio of poly(3,4-ethylenedioxythiophene)-poly(styrene sulfonic acid) to waterborne polyurethane prepolymer is 1:0.5. Everything else is the same as in Example 1.

[0034] Example 5 A composite polyester fiber differs from Example 1 in that the mass ratio of poly(3,4-ethylenedioxythiophene)-poly(styrene sulfonic acid) and waterborne polyurethane prepolymer is 1:4. Everything else is the same as in Example 1.

[0035] Comparative Example 1 A polyester fiber, differing from Example 1 in that: the first raw material contains 7 parts of aluminum diethylphosphinate. Otherwise, it is the same as Example 1.

[0036] Comparative Example 2 A polyester fiber, differing from Example 1 in that: the first raw material contains 15 parts of aluminum diethylphosphinate. Everything else is the same as in Example 1.

[0037] Comparative Example 3 A polyester fiber, differing from Example 1 in that the first raw material does not contain aluminum diethylphosphinate. Otherwise, it is the same as Example 1.

[0038] Comparative Example 4 A polyester fiber, differing from Example 1 in that the first raw material contains 1 part of nano-zinc oxide. Otherwise, it is the same as Example 1.

[0039] Comparative Example 5 A polyester fiber, differing from Example 1 in that the first raw material contains 5 parts of nano-zinc oxide. Otherwise, it is the same as Example 1.

[0040] Comparative Example 6 A polyester fiber, differing from Example 1 in that the first raw material does not contain nano-zinc oxide. Otherwise, it is the same as Example 1.

[0041] Comparative Example 7 A polyester fiber, differing from Example 1 in that the surface of the fiber body does not have a first coating. Otherwise, it is the same as Example 1.

[0042] Comparative Example 8 A polyester fiber, differing from Example 1 in that the first coating does not contain water-based polyurethane. Otherwise, it is the same as Example 1.

[0043] Comparative Example 9 A polyester fiber, differing from Example 1 in that: in the first coating, poly(3,4-ethylenedioxythiophene)-poly(styrenesulfonic acid) is replaced with polythiophene. Otherwise, it is the same as Example 1.

[0044] The following performance tests were performed on the polyester fibers obtained in Examples 1-5 and Comparative Examples 1-9: Elongation at break: in accordance with GB / T 14344-2022; Limiting oxygen index (LOI): determined according to GB / T 5455-2014; Surface resistivity: Tested according to GB / T 12703.4-2010, including the initial surface resistivity and the surface resistivity after 20 washes with conventional water.

[0045] The test results are shown in Table 1.

[0046] Table 1 Based on the data in Table 1, the limiting oxygen index of Comparative Example 1 was significantly lower than that of Example 1. This verifies the crucial impact of the amount of aluminum diethylphosphinate on flame retardant performance. When the amount of this component is insufficient, it is difficult to fully utilize the gas-phase free radical quenching and condensed phase char formation blocking effects, thus failing to effectively block the combustion chain reaction and directly causing a significant reduction in the flame retardant protection effect of the fiber.

[0047] Compared with Example 1, the elongation at break of Comparative Example 2 decreased significantly. This indicates that although the excessive addition of aluminum diethylphosphinate slightly improves the flame retardant properties, the excessive inorganic components easily form stress concentration sites inside the fiber matrix, destroying the continuous structure of the polymer molecular chain, resulting in the deterioration of the fiber's mechanical toughness and sacrificing its adaptability to textile processing.

[0048] Compared to Example 1, the limiting oxygen index of Comparative Example 3 was significantly reduced. This confirms the irreplaceable nature of aluminum diethylphosphinate as the core flame-retardant component. Without this component, the fiber loses its combustion-inhibiting ability and relies solely on the intrinsic flame-retardant properties of the matrix, resulting in a significant increase in flammability.

[0049] Compared to Example 1, the limiting oxygen index of Comparative Example 4 decreased. This reflects the auxiliary catalytic effect of nano-zinc oxide in the phosphorus-zinc synergistic flame retardant system. Insufficient dosage of nano-zinc oxide cannot efficiently catalyze the formation of a dense barrier char layer, and its synergistic effect with aluminum diethylphosphonate is significantly weakened.

[0050] Compared with Example 1, the elongation at break of Comparative Example 5 was significantly reduced. This reflects that excessive nano-zinc oxide is prone to particle aggregation, forming structural defects inside the fiber, destroying the mechanical stability of the matrix, and thus causing a decrease in fiber toughness.

[0051] Compared to Example 1, the limiting oxygen index of Comparative Example 6 was significantly reduced. This verifies the necessity of synergistic flame retardancy of nano-zinc oxide. Without this component, the char formation efficiency of a single flame retardant component is insufficient, making it difficult to construct a continuous and stable thermo-oxidative barrier layer, and the flame retardant protection capability is greatly reduced.

[0052] Compared to Example 1, the surface resistivity of Comparative Example 7 increased sharply. This highlights the core role of the poly(3,4-ethylenedioxythiophene)-poly(styrenesulfonic acid)-waterborne polyurethane composite coating in dissipating static charge. Without a functional conductive coating, the fibers cannot achieve rapid static discharge, and the antistatic function is completely ineffective.

[0053] Compared to Example 1, the surface resistivity of Comparative Example 8 increased significantly after water washing. This confirms the anchoring and protective function of waterborne polyurethane, which forms a stable conductive network with poly(3,4-ethylenedioxythiophene)-poly(styrenesulfonic acid) through hydrogen bonding. Without this film-forming component, the conductive structure is only attached by physical adsorption, which is easy to fall off during water washing and loses its long-term antistatic ability.

[0054] Compared with Example 1, the surface resistivity of Comparative Example 9 was significantly higher both initially and after water washing. This demonstrates the advantage of using specific conductive components in this application. Conventional polythiophene lacks hydrophilic sulfonic acid groups, has poor water dispersibility, cannot construct continuous conductive pathways, and has poor compatibility with waterborne polyurethane, making it difficult to form a stable and long-lasting antistatic coating system.

[0055] In the description of this specification, the terms "first" and "second" are used for descriptive purposes only and should not be construed as indicating or implying relative importance or implicitly specifying the number of indicated technical features. Thus, a feature defined as "first" or "second" may explicitly or implicitly include at least one of that feature.

[0056] The above description is only a preferred embodiment of this application. It should be noted that those skilled in the art can make several improvements and additions without departing from the method of this application, and these improvements and additions should also be considered within the scope of protection of this application.

Claims

1. A composite polyester fiber, characterized in that, Includes a fiber body and a first coating covering the surface of the fiber body; The fiber body is obtained by melt blending and spinning of a first raw material, which includes, by weight parts: 72-78 parts of polyethylene terephthalate chips, 6-10 parts of toughening agent, 9-13 parts of aluminum diethylphosphinate, 2-4 parts of nano zinc oxide, 1-2 parts of inorganic filler, and 1-1.5 parts of lubricant. The first coating comprises an aqueous polyurethane and poly(3,4-ethylenedioxythiophene)-poly(styrene sulfonic acid) uniformly dispersed in the aqueous polyurethane, wherein the aqueous polyurethane is obtained by crosslinking an aqueous polyurethane prepolymer.

2. The composite polyester fiber according to claim 1, characterized in that, The mass ratio of the poly(3,4-ethylenedioxythiophene)-poly(styrene sulfonic acid) and the waterborne polyurethane prepolymer is 1:(1-2).

3. The composite polyester fiber according to claim 1, characterized in that, The thickness of the first coating is 0.1μm-0.5μm.

4. The composite polyester fiber according to claim 1, characterized in that, The particle size of the aluminum diethylphosphonate is 0.5 μm-3 μm; And / or, the particle size of the nano zinc oxide is 50nm-80nm.

5. The composite polyester fiber according to claim 1, characterized in that, The intrinsic viscosity of the polyethylene terephthalate chips is 0.65 dL / g to 0.8 dL / g.

6. The composite polyester fiber according to claim 1, characterized in that, The toughening agent includes at least one of polycaprolactone, polybutylene succinate, and polybutene-1. And / or, the inorganic filler includes at least one of nano-calcium carbonate, nano-silica, nano-montmorillonite, and nano-talc. And / or, the lubricant comprises at least one of ethylene bis-stearamide, calcium stearate, zinc stearate, and pentaerythritol stearate.

7. The method for preparing composite polyester fiber according to any one of claims 1-6, characterized in that, Includes the following steps: The polyethylene terephthalate chips, the toughening agent, the aluminum diethylphosphinate, the nano zinc oxide, the inorganic filler, and the lubricant are mixed and then melt-blended and spun to obtain the fiber matrix. The poly(3,4-ethylenedioxythiophene)-poly(styrene sulfonic acid) and the aqueous polyurethane prepolymer are added to water, mixed well, and an impregnation solution is prepared. The fiber body is immersed in the impregnation solution, then removed, rolled, and dried to obtain the composite polyester fiber.

8. The method for preparing composite polyester fiber according to claim 7, characterized in that, The melt blending temperature in the melt blending spinning process is 265℃-280℃.

9. The method for preparing composite polyester fiber according to claim 7, characterized in that, The total mass of the poly(3,4-ethylenedioxythiophene)-poly(styrene sulfonic acid) and the waterborne polyurethane prepolymer in the impregnation solution accounts for 5%-10% of the total mass. And / or, the slurry rate of the roll is 60%-75%.

10. The method for preparing composite polyester fiber according to claim 7, characterized in that, The drying temperature is 120℃-135℃, and the drying time is 2min-10min.